Philippine English - Martin, Isabel Pefianco (Archīum Ateneo, 2020)
In this chapter, I approach English in the Philippines not as one language, but as several varieties that are used in a wide range of situations and contexts. English arrived in the country as a language transported through colonialism. Its spread was facilitated by a public education system led by young Americans who were deployed as teachers to far‐flung regions of the archipelago. The American English varieties that these teachers spoke came into contact with various Philippine lan- guages, resulting in the indigenization or nativization of English in the Philippines. This nativized variety, often referred to as “standard” or “educated” Philippine English, is the object of study of many language scholars. As English spread throughout the country, the language acquired new forms, features, and functions. It has also developed into a language of aspiration for many Filipinos. Language policies, largely disjointed and inchoate, have struggled to address the competing demands of the local and the global. In most cases, language policies persisted in promoting the “standard” English variety. What most studies and policies on English in the Philippines have continued to neglect is the fact that there are a variety of Englishes that multilingual Filipinos constantly use in a variety of situ- ations and contexts. In this chapter, I refer to these Englishes as Pinoylish – Philippine Englishes in constant flux, in continuous construction, always fluid, occupying various points in a cline of centrality and peripherality, drawing from a repertoire of local languages, including English as a Philippine mother tongue, as well as other modes of communication that shape what is meaningful to the Filipino.